PERANCANGAN PROTOTYPE SISTEM PENYEWAAN TANGKI TIMBUN (STORAGE TANK) CRUDE PLAM OIL (CPO) DAN PALM KERNEL OIL (PKO) - Martono Martono (LPPM STIKOM Dinamika Bangsa, 2020)
In the era of digitalization like now, the use of technology has penetrated into various aspects of life. The utilization of computer systems to support human work has become a commonplace thing. This also applies in the process of leasing a storage tank at PT XYZ. At present the storage tank rental system still uses a general program that only aimed at processing numbers. This certainly causes the currently existing rental system has several shortcomings, such as the unavailability of the function to control and report leasing of the existing storage tank. Based on these problems, the authors conducted a study entitled the prototype design of crude palm oil (CPO) storage tanks and palm kernel oil (PKO) systems. The system to be designed in this study was designed using waterfall modeling and use case diagrams. The rental system designed by this research has the function of changing user passwords, processing data such as user data, tanks, vehicles, customers, recipients, receipts and expenditures of palm oil, as well as reports on oil palm revenues and expenditures.